2020
DOI: 10.1021/acsabm.9b00984
|View full text |Cite
|
Sign up to set email alerts
|

Photocurable Albumin Methacryloyl Hydrogels as a Versatile Platform for Tissue Engineering

Abstract: Photopolymerization of protein-derived polymers functionalized with methacryloyl groups has been increasingly used to fabricate three-dimensional tissue constructs for biomedical applications because photocurable protein-based polymers (e.g., gelatin and collagen methacryloyl) feature spatial-temporal controllability of engineering complex constructs as well as inherent biological properties. Herein, we report photocurable albuminbased hydrogels. First, photocurable bovine serum albumin methacryloyl (BSA-MA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 68 publications
6
54
0
Order By: Relevance
“…In this study, all groups showed water content values similar to the human cornea (75%–85%) 45,48 . However, as previously reported in the literature, the mass swelling of SilkMA hydrogels decreased with higher polymer concentrations 10,49–51 . An increase in the concentration of photocrosslinkable groups results in a higher crosslinking density, which ultimately creates a tighter hydrogel network and a lower mass swelling ratio.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In this study, all groups showed water content values similar to the human cornea (75%–85%) 45,48 . However, as previously reported in the literature, the mass swelling of SilkMA hydrogels decreased with higher polymer concentrations 10,49–51 . An increase in the concentration of photocrosslinkable groups results in a higher crosslinking density, which ultimately creates a tighter hydrogel network and a lower mass swelling ratio.…”
Section: Discussionsupporting
confidence: 84%
“…Ferraci et al synthesized 10%, 15%, and 20% photocurable bovine serum albumin (BSA‐MA) with different degrees of substitution (DM = 73%–100%) using UV light (150 mW/cm 2 , 6 min). The compressive modulus of 15 and 20% BSA‐MA hydrogels with 92 DM% was ~18 and 30 kPa, respectively 10 . In this work, despite using a considerably lower DM% (40%) and intensity (3 mW/cm 2 ), the compressive modulus of 15% and 20% SilkMA hydrogels was 21 and 79 kPa, respectively.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations